FAKTOR-FAKTOR YANG MEMENGARUHI CONCEPTION RATE PADA SAPI BALI DI KABUPATEN PRINGSEWU - Frandy Febrianthoro; Madi Hartono; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this reserch are to know value conception rate and the factors and magnitude factors which disturb conception Rate of Bali Cattles in Pringsewu Regency. This Research was held on December 2014 until January 2015 by using Bali Cattles that had been inseminated of 100 farmers as much 131 Bali Cattles and secondary data IB result from 5 Inseminators. Data was analysis by multifactors regression with SPSS (Statistics Packet for Social Science) program. The result showed that Conception Rate of Bali Cattles at Pringsewu Regency is 50,38%.  Factors that affect the conception rate are the system of provision of  water that positively associated with factor value 0,255, shape of enclosure wall that negatively associated with  factor value 0,142; Age of Bali Cattles that negatively associated with factor value 0,015, service per conception  that negatively associated with factor value 0,295. Keywords : conception rates, Bali cattle, factors.